Game Fiksi Four Ghost Stories: Fiction Game Four Ghost Stories - Sumaki, Rangga; Kaunang, Sumenge T.G.; Sugiarso, Brave (Jurnal Teknik Elektro dan Komputer, 2024)
Abstract — Indonesia has various mythologies about mystical ghosts, ghost stories spread among society, namely Kuntilanak, Kuyang, Sundel Bolong, and Wewe Gombel. Ghost stories that spread in society originate from the culture of the society itself which reflects the cultural values ​​of that society. With games that can be a learning medium, this research was created with the aim of helping people understand the mythology of mystical ghosts in Indonesia. This game was created using an iterative method which has 4 stages. Based on the objectives of this research, the Fiction Game Four Ghost Stories application has been produced. This game is a 3D Horror genre. The game was created using the Unity game engine. Based on research that has been carried out, there are results from a questionnaire carried out in the first stage where participants answered questions about mystical ghost knowledge before playing the game with 8% correct results, with the second stage after playing the game answering 84% correct. Based on the results of the questionnaire, the game "Four Ghost Stories" was successfully made into an interesting game and was shown to be able to help people learn more about mystical ghost mythology in Indonesia. Key words— 3D Games; Iterative; Mystical Stories; Mythology; Unity   Abstrak — Indonesia memiliki berbagai macam mitologi tentang hantu mistis, kisah-kisah hantu yang tersebar di masyarakat yaitu seperti Kuntilanak, Kuyang, Sundel Bolong, dan Wewe Gombel. Cerita hantu yang tersebar di masyarakat berasal dari kebudayaan masyarakat itu sendiri yang mencerminkan nilai-nilai budaya masyarakat tersebut. Dengan game yang dapat menjadi media pembelajaran, penelitian ini dibuat dengan bertujuan untuk membantu masyarakat agar dapat memahami tentang mitologhi hantu mistis di Indonesia. Game ini dibuat dengan menggunakan metode Iteratif yang memiliki 4 tahap. Berdasarkan tujuan penelitian ini, sudah dihasilkan aplikasi Game Fiksi Four Ghost Stories. Game ini bergenre Horror 3D. Game dibuat menggunakan game engine Unity. Berdasarkan penelitian yang sudah dilakukan, terdapat hasil kuisioner yang dijalankan pada tahap pertama dimana peserta menjawab pertanyaan tentang pengetahuan hantu mistis sebelum memainkan game dengan hasil 8% benar, dengan tahap kedua sesudah memainkan game menjawab benar 84%. Berdasarkan hasil kuisioner, game “Four Ghost Stories” berhasil dibuat menjadi game yang menarik dan menunjukkan dapat membantu masyarakat lebih mengenal mengenai mitologi hantu mistis di Indonesia.  Kata kunci — Cerita Mistis; Game 3D; Iteratif; Mitologi; Unity